PERAN TOKOH MASYARAKAT DALAM MEMBANGUN PARTISIPASI POLITIK YANG BERKUALITAS DI DESA KERTASARI - Imani, Nafakhatul; Subiyanto; Tity Kusrina (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
This study aims to analyze the role of community leaders in promoting quality political participation in Kertasari Village, Suradadi District, Tegal Regency. The research focuses on: (1) the forms of roles carried out by community leaders, (2) the political communication strategies employed, and (3) the challenges faced in building citizens’ political awareness. This study adopts a qualitative approach with a descriptive case study design. Data collection techniques include interviews, observations, and documentation, analyzed using the Miles and Huberman model. The findings reveal that: (1) community leaders serve as educators, mediators, and moral role models through informal spaces such as religious gatherings, community meetings, and personal communication; (2) the strategies applied are persuasive and contextual, considering citizens’ social backgrounds and levels of political literacy; and (3) participation challenges include political apathy, transactional influences, and limited access to information. To address these issues, community leaders employ cultural approaches and exemplary conduct. These findings reinforce the strategic position of community leaders in fostering political participation that is not merely formal, but also substantive and reflective